Nutritional and economic potential of Clarias liocephalus for rural populations of South Western Uganda - YATUHA, J.; KANG’OMBE, J.; NKWANGU, D; AKOLL, P; MASEMBE, C (African Journal of Rural Development, 2019)
Southwestern Uganda is one of the densely populated and nutritionally insecure regions in Uganda. The motivation behind this study was to explore the potential of Clarias liocephalus, a small wetland fish species common in the area, as source of nutritious food and supplementary income to the nutritionally and economically strained communities in the region. Although this fish has been part of the diet in some rural households in Uganda, information on its nutritional prowess and potential to address rural malnutrition and boost household income is still scanty. Macronutrients crude protein, crude fat, moisture, ash and mineral calcium and selected micronutrients, i.e., iron, zinc and manganese of C. liocephalus carcasses were analysed following AOAC standard methods. The general views of the fishers and users on the economic attributes of C. liocephalus in the region were also broadly evaluated. Results on the nutritional value (presented on wet weight basis) show C. liocephalus as a high protein-low fat fish (15.2±0.191 and 0.301±0.031, respectively); offering a nutritional advantage to protein deficient and fat controlling diets in the community. It is also a key source of essential micronutrients highly desired in human nutrition (Calcium 715.225; Zn 2.080; Fe 5.370 and Mn 0.151). The high iron content is an important remedy against nutritional anaemia which is especially common in poor households in the study region. The community attaches several attributes to this fish in the diet but the quick money obtained from immature fish sold as bait has steadily diminished it from people’s tables. We advocate for inclusion of this fish in peoples diets and recommend management intervention to limit the trade in immature C. liocephalus. We recommend further investigation into the wider nutritional profile and domestication trials of C. liocephalus
Keywords: Clarias liocephalus; Fish; Malnutrition; Micronutrients; Uganda; Wetland